2010
DOI: 10.1111/j.1749-6632.2010.05665.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based management of poor ovarian response

Abstract: Poor ovarian response is not infrequent and represents one of the major therapeutic challenges in in vitro fertilization. Although several tests have been proposed, which aim at predicting poor response to ovarian stimulation, available data are conflicting regarding their accuracy and clinical usefulness. Even though several therapeutic approaches have been explored, a single effective strategy has not yet been established. One of the major limitations of interpreting the relevant literature is the wide varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 34 publications
0
30
0
3
Order By: Relevance
“…Poor response to superovulation is a major hurdle in the treatment of infertility in women by in vitro fertilization (IVF) and affects between 9% and 24% of patients [37]. While many epidemiological studies have identified contributing factors such as age, basal gonadotropin levels, and basal sex steroid levels, they cumulatively have only small predictive value for the response rate [37]. The superovulation phenotype observed in Snf2l Ex6DEL mice suggests that SNF2L may play a role in human fertility, and that future studies should focus on evaluating SNF2L as a prognostic indicator for IVF success and should screen refractory patients for genetic alterations at the Snf2l locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor response to superovulation is a major hurdle in the treatment of infertility in women by in vitro fertilization (IVF) and affects between 9% and 24% of patients [37]. While many epidemiological studies have identified contributing factors such as age, basal gonadotropin levels, and basal sex steroid levels, they cumulatively have only small predictive value for the response rate [37]. The superovulation phenotype observed in Snf2l Ex6DEL mice suggests that SNF2L may play a role in human fertility, and that future studies should focus on evaluating SNF2L as a prognostic indicator for IVF success and should screen refractory patients for genetic alterations at the Snf2l locus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a better understanding of the role of SNF2L in superovulation may open up diagnostic or therapeutic avenues for the common clinical problem of poor response to gonadotropins in fertility patients [35,36]. Poor response to superovulation is a major hurdle in the treatment of infertility in women by in vitro fertilization (IVF) and affects between 9% and 24% of patients [37]. While many epidemiological studies have identified contributing factors such as age, basal gonadotropin levels, and basal sex steroid levels, they cumulatively have only small predictive value for the response rate [37].…”
Section: Discussionmentioning
confidence: 99%
“…Poor ovarian responders are not easy to manage and despite utilising various protocols of GnRH agonists alone or with drugs like letrozole, pyrigostigmine, growth hormone, growth hormone releasing factor and oral L-arginine, a single effective strategy remains to be established [7].…”
Section: Drugs For the Clinical Management Of Female Infertilitymentioning
confidence: 99%
“…Tatone et al investigated the previous study showing that, according to the most relevant concept of ageing, ovarian age-associated malfunction results from physiological accumulation of irreparable damages of biomolecules as an unavoidable side effect of normal metabolism [3]. Despite the advances in science and technology, the management of poor responder patients after ovarian stimulation in in vitro fertilization (IVF) is still considered as one of the most urgent problems, because the small number of female gametes obtained in poor responder patients is associated with a significantly reduced probability of realization of pregnancy [4]. In 1983, Garcia et al gave the first definition of poor responder patients to ovarian stimulation [5].…”
Section: Introductionmentioning
confidence: 99%